Chlorpromazine in the treatment of schizophrenia and manic depression - Querol, Mariano (1957)
The results of treatment with chlorpromazine (Largactil) -a dose of 100 to 600 mg regimen are presented. daily, alone or combined with sedatives and electroplexia, for the time necessary to obtain a change in symptoms or for a minimum of three months, without attempting a cure of sleep cause in 26 schizophrenic patients, of various types, and 6 manic , of which 5 were in manic depressive phase, 1-anxious to begin the healing phase. All patients had more than 6 months of illness; Schizophrenics and 22 manic all had more than one year of disease. In all cases of schizophrenia treatments were applied pre-emergence but no improvement then treated with chlorpromazine was obtained. The results were: among schizophrenics 7 complete remissions, 4 social referrals, 6 improvements, 8 no improvement and 1 death; among patients with manic psychosis 4 complete remissions and 2 deaths. Influenced symptoms both in terms schizophrenic manic, were side, although the primary symptoms were changed. The results obtained suggest that chlorpromazine should be considered a fundamental treatment in these endogenous psychoses, particularly as the results obtained with it are improvements to those achieved with other treatments in earlier phases of manic-depressive psychosis and in the same outbreak schizophrenia. Presents and discusses the complications and causes of death, with emphasis on the acceptance of the treatment by patients.